2017
DOI: 10.1016/j.jisp.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Replenishing Regulatory T Cells to Halt Depigmentation in Vitiligo

Abstract: Vitiligo is a cutaneous autoimmune disease, especially devastating to patients with darker skin tones because of the contrast between unaffected and lesional skin. We studied immune cells infiltrating vitiligo skin and found very few regulatory T cells (Tregs). Vitiligo was not associated with a reduced frequency or function of circulating Tregs. To manipulate Treg function, we used mouse models expressing melanocyte-reactive TCRs, following changes in pelage color. We also isolated splenocytes to measure Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 101 publications
(103 reference statements)
2
39
0
4
Order By: Relevance
“…In addition, decreased expression of FOXP3, HELIOS, and EOS in PBMCs of vitiligo patients supported our proposed mechanism of Th17 cell predominance and Treg cell downregulation. Moreover, a recent study reported very few Tregs in vitiligo skin and found chemokine CCL22 is responsible for attracting circulating Tregs . Collectively, the study supported our results, showing a lower number of Tregs in vitiligo skin.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, decreased expression of FOXP3, HELIOS, and EOS in PBMCs of vitiligo patients supported our proposed mechanism of Th17 cell predominance and Treg cell downregulation. Moreover, a recent study reported very few Tregs in vitiligo skin and found chemokine CCL22 is responsible for attracting circulating Tregs . Collectively, the study supported our results, showing a lower number of Tregs in vitiligo skin.…”
Section: Discussionsupporting
confidence: 91%
“…83 Transfer of Treg cells into a vitiligo mouse model or treatment with rapamycin, which is known to promote Treg cell function, markedly reduced depigmented lesions. 84 Functional impairment of Treg cells was also observed in the C3H/HeJ mouse model of AA 85 and in human patients with AA. 12,[85][86][87][88][89][90] Injections of low doses of IL-2 into the scalp skin of human patients with AA increased the number of Treg cells in the scalp skin and reportedly induced partial hair growth.…”
Section: Is Aa a Model Disease For An Imbalance Between Cytotoxic Effmentioning
confidence: 90%
“…78 Treg cells are essential regulators of the immune system, and their alteration in number and function has been implicated in several inflammatory diseases. [79][80][81][82][83][84] Therefore a defect in Treg cell function has piqued the interest of investigators in the context of AA pathogenesis. 12,[85][86][87][88][89] Given that the eye is one of the major immune-privileged sites of mammals, key pointers arise from ophthalmologic research, and HF IP research might also inform human eye IP research.…”
Section: Is Aa a Model Disease For An Imbalance Between Cytotoxic Effmentioning
confidence: 99%
“…Currently, Janus kinase (JAK) inhibitors that interfere with IFN‐γ signalling are in clinical trials . A tolerizing version of heat shock protein 70, Treg promoting treatment and antibodies that interfere with T‐cell recruitment are some promising new approaches that might be translated to the clinic. In the arena of therapeutics, it is important to consider that pathways may be affected in some patients and not in others, and that this can and should impact treatment choices.…”
Section: Discussionmentioning
confidence: 99%